Twenty-First International Conference on Thermoelectrics, 2002. Proceedings ICT '02.
DOI: 10.1109/ict.2002.1190357
|View full text |Cite
|
Sign up to set email alerts
|

A study of heat sink performance in air and soil for use in a thermoelectric energy harvesting device

Abstract: A suggested application of a thermoelectric generator is to exploit the natural temperature difference between the air and the soil to generate small amounts of electrical energy. Since the conversion efficiency of even the best thermoelectric generators available is very low, the performance of the heat sinks providing the heat flow is critical. By providing a constant heat input to various heat sinks, field tests of their thermal conductances in soil and in air were performed. A prototype device without a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Thermoelectric generators have been used for capturing ambient energy in various applications. Lawrence and Snyder [62] suggest a potential method of retrieving electric energy from the temperature difference that exists between the soil and the air. The results showed that a maximum instantaneous power of approximately 0.4 mW could be generated.…”
Section: Converting Thermal Energy To Electrical Energymentioning
confidence: 99%
“…Thermoelectric generators have been used for capturing ambient energy in various applications. Lawrence and Snyder [62] suggest a potential method of retrieving electric energy from the temperature difference that exists between the soil and the air. The results showed that a maximum instantaneous power of approximately 0.4 mW could be generated.…”
Section: Converting Thermal Energy To Electrical Energymentioning
confidence: 99%
“…Some research has been done on exploiting the temperature difference between the air and earth to generate electrical power [7,8]. Temperature differences of about -0.35° to 0.7°C were measured.…”
Section: Introductionmentioning
confidence: 99%
“…et al (2004). In the research area of thermal energy harvesting, both Stevens Stevens (1999) and Lawrence et al Lawrence et al (2002) consider the system design aspects for thermal energy scavenging via thermoelectric conversion that exploits the natural temperature difference between the ground and air. Similarly, Leonov et al Leonov et al (2007) have considered thermal energy harvesting through thermoelectric power generation from body heat to power www.intechopen.com wireless sensor nodes.…”
Section: Various Energy Harvesting Techniquesmentioning
confidence: 99%